STAT3 activation is a critical step in gp130-mediated terminal differentiation and growth arrest of a myeloid cell line. - Minami, M (1996)
Myeloid leukemia M1 cells can be induced for growth arrest and terminal differentiation into macrophages in response to interleukin 6 (IL-6) or leukemia inhibitory factor (LIF). Recently, a large number of cytokines and growth factors have been shown to activate the Janus kinase (JAK)-signal transducer and activator of transcription (STAT) signaling pathway. In the case of IL-6 and LIF, which share a signal transducing receptor gp130, STAT3 is specifically tyrosine-phosphorylated and activated by stimulation with each cytokine in various cell types. To know the role of JAK-STAT pathway in M1 differentiation, we have constructed dominant negative forms of STAT3 and established M1 cell lines that constitutively express them. These M1 cells that overexpressed dominant negative forms showed no induction of differentiation-associated markers including Fc gamma receptors, ferritin light chain, and lysozyme after treatment with IL-6. Expression of either c-myb or c-myc was not downregulated. Furthermore, IL-6- and LIF-mediated growth arrest and apoptosis were completely blocked. Thus these findings demonstrate that STAT3 activation is the critical step in a cascade of events that leads to terminal differentiation of M1 cells.